Practical Bot Development Designing and Building Bots with Node.js and Microsoft Bot Framework - Rozga, Szymon (Apress, 2018)
Explore the concept of bots and discover the motivation behind working with these new apps with messaging platforms. This book is an accessible resource teaching the basic concepts behind bot design and implementation. Each chapter builds on previous topics and, where appropriate, real working code is shown that implements the concepts. By just picking up a code editor, you can start creating smart, engaging, and useful bot experiences today. Practical Bot Development will teach you how to create your own bots on platforms like Facebook Messenger and Slack, incorporate extension APIs, and apply AI and ML algorithms in the cloud. By the end of this book, you'll be equipped with the information to reach thousands of new users with the bots you create! The book is a great resource for those looking and harness the benefits of building their own bots and leveraging the platform feasibility of them.